Iconicity in illustration for their representation in document databases - Castillo-Vidal, Jesús (Anuario ThinkEPI, 2012)
Searching for images requires procedures that go beyond the mere recognition of shapes, colors and other aspects of automatic indexing. Image analysis is needed that measures the degree of abstraction or the reproduction of reality, especially when it comes to artistic performances. We present some basic ideas about making it possible to express quantitatively the degree of approximation of the real object of an image so that this factor can be used in automatic document retrieval.